Web-Based General Election Information System Using e-Voting at the Institut Pendidikan Indonesia - Ilham Gerhana; Rizki Ramdhani; Yopi Nugraha; Purnomo Sidiq (RISTEC : Research in Information Systems and Technology, 2020)
Abstract: Electronic voting or e-voting implemented at the Indonesian Institute of Education Garut is a form of voting that is usually used for general elections and polls using electronic media. The times have made a shift in the use of media from conventional to digital. Many innovations are used in this technological era, especially web information systems. The use of this web information system is currently widely used for electronic voting because of the speed and security of the data generated. This electronic voting information system or term in this technological era is called e-voting using website technology designed very simply and relatively cheaply so that voting at the Garut Indonesian Institute of Education which was previously manual can be done digitally by using information system technology. web. Keywords: E-voting; Information Systems; Web Abstrak: Pemungutan suara elektronik atau e-voting yang diterapkan di Institut Pendidikan Indonesia Garut adalah suatu bentuk pemungutan suara yang biasanya digunakan untuk pemilihan umum maupun poling menggunakan media elektronik. Perkembangan zaman, membuat pergeseran  penggunaan media yang dahulu konvensional menjadi digital. Banyak inovasi yang digunakan di era teknologi ini terutama yaitu sistem informasi web. Penggunaan sistem informasi web ini  saati ini banyak dipakai  untuk pemungutan suara elektronik karena kecepatan, dan keamanan data yang dihasilkan. Sistem informasi pemungutan suara elektronik ini  atau istilah di era teknologi ini bernama e-voting  menggunakan teknologi website dirancang dengan sangat sederhana dan biaya yang relatif murah agar pemungutan suara di Institut Pendidikan Indonesia Garut yang tadinya manual bisa dilakukan dengan secara digital yaitu dengan menggunakan teknologi sistem informasi web. Kata kunci: E-voting; Sistem Informasi; Web